Simulation‐Optimization Models for the Dynamic Berth Allocation Problem. (17th September 2013) - Arango, Carlos; Cortés, Pablo; Onieva, Luis; Escudero, Alejandro
Abstract: Container terminals (CTs) are designed to provide support for the continuous changes in container ships. The most common schemes used for dock management are based on discrete and continuous locations. In view of the steadily growing trend in increasing container ship size, more flexible berth allocation planning is mandatory. The consideration of continuous location in the CT is a good option. This article addresses the berth allocation problem with continuous dock, which is called dynamic berth allocation problem. We propose a mathematical model and develop a heuristic procedure, based on a genetic algorithm, to solve the corresponding mixed integer problem. Allocation planning aims to minimize distances traveled by the forklifts and the quay crane, for container loading and unloading operations for each ship, according to the quay crane scheduling. Simulations are undertaken using Arena software, and experimental analysis is carried out for the most important CT in Spain.